Prescription patterns of antidementives in a high income country: A pharmacoepidemiologic study. Issue 1 (29th April 2020) - Wurm, Raphael; Stamm, Tanja; Reichardt, Berthold; Schwarz, Felix; Parvizi, Tandis; Silvaieh, Sara; König, Theresa; Cetin, Hakan; Stögmann, Elisabeth
Abstract: Introduction: Dementia is a leading and growing cause of morbidity and mortality. The aim of this study was to investigate real‐world prescription patterns of antidementive medication in one of the largest cohorts published thus far to optimize use in this growing population. Methods: Prescription claims from 2005 to 2016 were provided by Austrian sickness funds, covering 98% of the population of Austria. Patients treated with at least one of the four approved antidementive drugs (ADDs) were included. Prescription prevalence was calculated for 2014 and 2015, and prescription patterns were traced on an individual level during the entire study period. Results: A total of 127, 896 patients were treated with an ADD between 2005 and 2016. The prevalence was 0.93% in 2014 and 1% in 2015. The median age at initiation of treatment was 82.3 years, and 65% were female. Initial therapy was a cholinesterase inhibitor (ChEI) in 80% and memantine in 20%. The median duration of therapy was 13.3 months. Eighteen percent of patients switched medication: two thirds to receive memantine, and one third to a different cholinesterase inhibitor. More than 26% discontinued treatment early. Conclusion: We find that discontinuation of ADDs is more frequent than switching; memantine is a common starting drug and age at the start of treatment is rather high in this population. Interpretation should be cautious, but the data may suggest that treatment guidelines are followed inconsistently. Appropriate provision of the available options should be emphasized to optimize cognitive survival, comorbidity, quality of life, and health care expenditures.